3-(4-Methylthiophenyl)acetylacetone – ups and downs of flexibility in the synthesis of mixed metal–organic frameworks. Ditopic bridging of hard and soft cations and site-specific desolvation. Issue 6 (14th January 2020) - Gildenast, Hans; Nölke, Stephanie; Englert, Ulli
Abstract : Different Pearson-hardness of O and S donors leads to well-ordered mixed metal–organic frameworks. Abstract : 3-(4-Methylthiophenyl)pentane-2, 4-dione (HacacSMePh) combines a Pearson-hard β-diketone and a soft thioether group in its periphery; after deprotonation, it may act as a heterobifunctional linker between metal cations. Coordination of the β-diketo site to trivalent cations afforded a series of M(acacSMePh)3 metal complexes with dangling thioether moieties. Crosslinking of the mononuclear M(acacSMePh)3 building units via the SMe functionalities with Ag I cations resulted in mixed metal–organic frameworks (MMOFs). All bimetallic networks with M III = Co, Al, Cr, Fe, Ga are isostructural. Statistical occupancy of the M III site by two different cations may be possible and has been proven for Al III and Ga III . The MMOFs are semiporous and contain two co-crystallized chloroform molecules in the asymmetric unit. One of these CHCl3 molecules may be partially removed while maintaining the structural integrity of the network.